2021
DOI: 10.1177/17423953211065006
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Professionals’ Experiences of Facilitating Patient Activation and Empowerment in Chronic Illness using a Person-Centered and Strengths-Based Self-Management Program

Abstract: Objective Patients with chronic illness who are empowered and activated are more likely to engage in self-management in order to stabilise their condition and enhance their quality of life. This study aimed to explore Health Care Professional's (HCP) assessment of a person-centered intervention called ‘The Bodyknowledging Program’ (BKP) for the facilitation of empowerment and patient activation in the context of chronic illness. Methods This study employed a qualitative process evaluation after programme compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Studies have shown that patient participation leads to active health promotion, heightened self-care awareness, and the continuous enhancement of self-care skills. 4 , 16 In this study, the ESCA scale was used to evaluate the self-care abilities of both groups of patients. Results demonstrate that the Healthcare Guidance Program significantly improved the self-care abilities of patients with decompensated hepatitis B cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that patient participation leads to active health promotion, heightened self-care awareness, and the continuous enhancement of self-care skills. 4 , 16 In this study, the ESCA scale was used to evaluate the self-care abilities of both groups of patients. Results demonstrate that the Healthcare Guidance Program significantly improved the self-care abilities of patients with decompensated hepatitis B cirrhosis.…”
Section: Discussionmentioning
confidence: 99%